The nineteenth-century British Jesuits, with special reference to their relations with the vicars apostolic and the bishops - L'Estrange, P; L'estrange, Peter John (1991)
﻿ This thesis sets out to examine the relations between the Society of Jesus, the Roman Catholic religious order known as the Jesuits, and the Vicars Apostolic and Bishops during the nineteenth-century. Suppressed in 1773 by the Pope, the Jesuits were restored at the beginning of the nineteenth-century and became the largest group among the Regular clergy in the United Kingdom. They possessed a reputation which provoked strong reactions both within and beyond the Roman Catholic community. The thesis concentrates on the relations during the protracted restoration of the Jesuits, which occurred during the struggle for full Roman Catholic emancipation, and on the various disputes (mainly concerned with the Bishops' jurisdiction and the exempt status of Regulars) which arose between the restoration of the Hierarchy in 1850 and 1881, in which year Rome provided a new constitution, Romanes Pontifices. which governed the relations between Bishops and the Regular clergy. Discussion is concentrated on the Jesuits' relations with Henry Manning in Westminster and Herbert Vaughan in Salford, in whose diocese the Jesuits attempted to open a college in Manchester; attention is also given to John Henry Newman, who, whilst not a diocesan Bishop, was a figure of related significance in this context. The interrelationship between the respective attitudes of these men to the Jesuits, and Jesuit views of them, forms the central focus of the thesis. It illuminates the central problem of the Jesuits' identity and activity in the nineteenth century, and reveals the continuity of nineteenth-century disputes with earlier conflicts on the English mission.